Comparación del plano oclusal anterior y posterior entre pacientes de sexto y séptimo año de básica de la escuela fiscal "Fray Jodoco Ricke" con maloclusión clase dos subdivisión 1 y oclusión clase uno - Riofrío Reyes, Wendy Carolina (2017)
The objective of this study was to determine the occlusal plane and to relate it to the type of growth. A sample of 90 patients were selected from 42 patients, 5 class one and 36 patients, class two subdivision 1, men and women between the ages of 9 and 14 who had not received previous orthopedic or orthodontic treatment. The sample was taken at the fiscal school "Fray Jodoco Ricke" located in the town of Lumbisí. Extraoral and intraoral clinical photographs were taken as well as study models and panoramic and lateral cephalic radiographs. The X-rays were taken with the same cephalostat of the house moritaveraviewepocs 2D, operated by the same operator standardizing the position of the head. Cephalometrics were performed using the Dolphin DIGITAL Imaging System software by a single executor. The results were tabulated with the statistical program SPSS Stadistics, which showed that there is a relationship between the occlusal plane and the facial pattern, the patients with the highest percentage were dolichofacial with prevalence of class two patients taking into account both ANB and A-NPg by retrusion Mandibular skeletal and excessive anterior vertical growth. It was concluded that there is an inclination of the occlusal plane downward in this type of patients.